2003
DOI: 10.1016/s0167-6296(03)00022-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal employment and overweight children

Abstract: This paper seeks to determine whether a causal relationship exists between maternal employment and childhood weight problems. We use matched mother-child data from the National Longitudinal Survey of Youth (NLSY) and employ econometric techniques to control for observable and unobservable differences across individuals and families that may influence both children's weight and their mothers' work patterns. Our results indicate that a child is more likely to be overweight if his/her mother worked more hours per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
392
14
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(435 citation statements)
references
References 25 publications
23
392
14
6
Order By: Relevance
“…The relationship between the employment status of parents and children's weight status has been the subject of several studies during the past decade [32] [33] [45] [49]- [56]. There may be a positive and significant relationship between the average number of hours a mother works per week and overweight in children, but this relationship is not systematic and varies, depending on the age of children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the employment status of parents and children's weight status has been the subject of several studies during the past decade [32] [33] [45] [49]- [56]. There may be a positive and significant relationship between the average number of hours a mother works per week and overweight in children, but this relationship is not systematic and varies, depending on the age of children.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' education level was classified by the highest level of education attained by the father and mother and was defined according to the International Standard Classification of Education (ISCED) in 3 classes: primary, secondary and tertiary education. The status of occupational activity (active or not) was used to consider time costs related to parents' foodrelated decisions and parents' ability to acquire quality food and provide recreational activities outside the home [32] [33]. Occupational statuses were defined as a dichotomous variable.…”
Section: Socioeconomics Variablesmentioning
confidence: 99%
“…Parents' fatigue, stress, and depression may be important channels through which nonstandard shifts are related to children's BMI (Morrissey, Dunifon, and Kalil 2011). Parents who are sleep-deprived or stressed may be less likely to plan mealtimes and more likely to rely on fast or prepared food (Devine et al 2006;J abs et al 2007), w hic h could unfavorably influence childre n's BMI (Anderson, Butcher, and Levine 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, maternal work may be positively or negatively associated with childhood obesity (Hong and White-Means 1993). On one hand, working mothers were less likely to spend time with their children, including time preparing meals, eating meals as a family, and engaging children in outdoor activities (Anderson et al 2003;Bauer et al 2012;Cawley and Liu 2007;Fertig et al 2009;Moro-Egido 2012). Furthermore, working mothers tended to leave their children in nonparental care where the nutritional quality of foods and the level of physical activity tended to be lower than those with parents (Cesur et al 2010;Maher et al 2008;Padget and Briley 2005;Story et al 2006;You and Davis 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, empirical evidence has been inconsistent. For example, several studies found a positive correlation between maternal work and children's likelihood of being obese, especially among children in high-income families with a well-educated or White mother (Anderson et al 2003;Fertig et al 2009;Ruhm 2008). Other studies found that the deleterious effect of mothers' work was salient only among low-income families (Chia 2008;Miller 2011;Morrissey et al 2011;Scholder 2008).…”
Section: Introductionmentioning
confidence: 99%